Cardiorespiratory Coordination in Hypercapnic Test Before and After High-Altitude Expedition - Gultyaeva, Valentina V.; Uryumtsev, Dmitriy Y.; Zinchenko, Margarita I.; Melnikov, Vladimir N.; Balioz, Natalia V.; Krivoschekov, Sergey G. (Frontiers in Physiology, 2021)
Coordination of cardiovascular and respiratory systems provides a wide range of human adaptation and depends upon the functional state of an individual organism. Hypoxia is known to elicit changes in oxygen and carbon dioxide sensitivity, while training alters cardiorespiratory coordination (CRC). Delayed effect of high altitude (HA) acclimatization on CRC in mountaineers remains unknown. The objective of this study was to compare CRC in acute hypercapnia in mountaineers before and after HA expedition. Nine trained male mountaineers were investigated at sea level before (Pre-HA) and after a 20-day sojourn at altitudes of 4000-7000 m (Post-HA) in three states (Baseline, Hypercapnic Rebreathing and Recovery). A principal component (PC) analysis was performed to evaluate the CRC. The number of mountaineers with one PC increased Post-HA (nine out of nine), compared to Pre-HA (five out of nine) (Chi-square (df =1) = 5.14, P=0.023); the percentage of total variance explained by PC1 increased (Pre-HA median 65.6 (Q1 64.9/Q3 74.9), Post-HA 75.6 (73.3/77.9), P =0.028). Post-HA, the loadings of expired fraction of O2, CO2, and ventilation onto PC1 did not change, the loading of heart rate increased (Pre-HA 0.64 (0.45/0.68), Post-HA 0.76 (0.65/0.82), P =0.038). During the Recovery, the percentage of total variance explained by PC1 was higher than during the Baseline. Post-HA, there was a high correlation between the Exercise addiction scores and the eigenvalues of PC1 (r=0.9, P=0.001). Thus, acute hypercapnic exposure reveals the Post-HA increase in cardiorespiratory coordination, which is highly related to the level of exercise addiction.